Effects of Peer Tutoring to The Learning Outcomes in Exponential Expressions of Grade 8 Students - Ycong, Helmar G; Barredo, Bayron S; Mamolo, Leo A (Universitas Sarjanawiyata Tamansiswa, 2021)
Achieving the learning outcomes set for the classroom is the main goal of instruction. Todays’ teachers utilize various methods to achieve optimum learning for the students. This study investigated the effect of peer tutoring strategy on the students’ achievement in solving exponential expressions. It also determined the students’ persistent errors in solving given exponential expressions. This study employed a quasi-experimental design and two intact classes randomly assigned to an experimental and control group. A validated 10-item test (α=.75) was utilized as the main instrument. Results revealed that students in the peer tutoring group performed better than in the lecture group. Moreover, the peer tutoring strategy significantly improved the learning outcomes of students in the experimental group. It is recommended that peer tutoring strategy may be used by mathematics teachers to improve their students' performance in the subject matter. Implications address the need to explore other teaching strategies suited for students in the Mathematics classroom.